Performance of Instagram Social Media Marketing in the Great Asia Africa Lembang, Bandung Barat District - Arianis Chan; Margo Punomo; Arif Hernowo (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: The megashifting industry encourages tourism to be able to survive in the face of crises and create a new balance with new management systems and activities. One of the new changes, namely Accelerated Digitalization or the acceleration of digitization and the pandemic, has encouraged consumers to switch to the digital/online realm. This is also used by The Great Asia Africa Lembang, one of the tourist destinations in West Bandung Regency that uses social media marketing as a medium to promote the uniqueness of existing attractions. This study examines the influence of Social Media Marketing (SMM) on the decision to visit The Great Asia Africa Lembang, West Bandung Regency. Design/methodology/approach: The method used in the research in this journal uses quantitative methods that are analyzed by alternative partial least squares (PLS) with a sample of 270 respondents. Findings: The findings in this study indicate that the performance of social media marketing in The Great Asia Africa Lembang, West Bandung Regency is categorized as strong with each QMS dimension that forms the construct significantly. Based on the four dimensions that make up, content creation is the dominant dimension, this shows that the content created by The Great Asia Africa can be accepted by the public as a source of tourism information. Research limitations/implications: The limitation in this study is that it only uses a sample of Instagram followers from The Great Asia Africa, so it is necessary to expand the reach of the population to get a more diverse response. Practical implications: Based on the four dimensions that make up, content creation is the dominant dimension, this shows that the content created by The Great Asia Africa can be accepted by the public as a source of tourism information. Originality/value: This paper is original Paper type: a Research Paper